Development and evaluation of immunogenicity and protective efficacy of two recombinant attenuated newcastle disease viruses expressing the VP2 protein of infectious bursal disease virus - Xiaolong Fan; Bolong Li; Lijing Zhu; Yuanmeng Shen; Han Zhou; Guojie Ding; Jiaxuan Li; Yanping Jiang; Wen Cui; Lijie Tang; Shuo Jia; Yijing Li (Poultry Science)
Newcastle disease (ND) and Infectious bursal disease (IBD) are highly contagious and economically significant viral diseases affecting poultry worldwide. Despite widespread vaccination, current vaccines often require multiple doses and provide limited protection against emerging strains. This study developed and evaluated bivalent vaccines based on recombinant Newcastle disease virus (NDV) expressing the VP2 protein of a novel variant Infectious bursal disease virus (IBDV), SHG19 strain. To enhance immunogenicity and antigenic compatibility, two recombinant NDVs were generated: rHV, using a modified genotype VII HEB strain backbone, and rLHV, using the lentogenic LaSota backbone incorporating HEB F and HN genes. Protective efficacy was evaluated in specific pathogen-free (SPF) chickens through immunization followed by challenges with both NDV and IBDV. Results demonstrated robust humoral immune responses, significant reductions in viral shedding, and effective dual protection against both pathogens. These findings highlight the potential of NDV-based bivalent vaccines to streamline vaccination protocols and offer enhanced protection against circulating NDV and IBDV strains.